2018
DOI: 10.1080/10803548.2018.1466508
|View full text |Cite
|
Sign up to set email alerts
|

Safety challenges and improvement strategies of ethnic minority construction workers: a case study in Hong Kong

Abstract: Due to cultural differences, ethnic minority construction workers are more difficult to manage and more vulnerable to accidents. This study aims to identify the major barriers faced by ethnic minority workers from their own perspectives and to determine potential strategies to enhance the safety climate of construction projects, thus ultimately improving their safety performance. A survey with the modified nordic safety climate questionnaire was conducted for a certain subcontractor in Hong Kong. In-depth inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Thus, the model satisfied the assumption of proportionality or parallelism of odds. Moreover, to measure the strength of association between the five IVs and the DV using Equations (10)(11)(12), the model demonstrated acceptable levels of pseudo R 2 s: Cox and Snell = 0.143, Nagelkerke = 0.178, and McFadden = 0.095, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the model satisfied the assumption of proportionality or parallelism of odds. Moreover, to measure the strength of association between the five IVs and the DV using Equations (10)(11)(12), the model demonstrated acceptable levels of pseudo R 2 s: Cox and Snell = 0.143, Nagelkerke = 0.178, and McFadden = 0.095, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…A study that took place in Morocco's construction industry, which endures low safety performance, found that a positive safety climate appears to counteract the negative effect that high-risk tolerance imposes on safety behavior [10]. Ethnic minority construction workers are vulnerable to accidents, which emphasizes the importance of determining potential strategies to improve construction sites' safety climate that will lead to improved safety performance [11]. Moreover, the safety climate can assist industry owners and contractors by providing information related to attitudes and perceptions, which can promote enhanced safety performance [12].…”
Section: Introductionmentioning
confidence: 99%
“…Globally Pakistan was ranked the 9th populated country in 2017, with the total labor force of 54.9 million (Government of Pakistan, 2018). Every year, an occupational injury/ incidences, 41 workers out of 1000 received an injury in the construction companies of Pakistan (Wu, Luo, Wang, Wang, & Sapkota, 2018).…”
Section: Construction Industry In Pakistanmentioning
confidence: 99%
“…The activities of traditional cultural development, through the independent participation and display of students, improve the music theory and cultural knowledge learned in the previous period, and experience and explore a wider range of national culture. [3] Organizing ethnic music activities is a more vivid and acceptable way to enrich students' musical literacy. Such small ethnic music activities can not only cultivate students' love for music, but also inject the national spirit into the life of students in a more lively way.…”
Section: Organizing National Music Activities Is An Aidmentioning
confidence: 99%